Analisis Pengaruh Pendidikan dan Pengangguran Terhadap Kemiskinan di Propinsi Nusa Tenggara Timur Tahun 2008 – 2013 - Yuniarti Reny Renggo (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2015)
Poverty is an issue that involves many aspects of life because it is usually associated with low income, illiteracy, poor health status and inequality between the sexes and poor environment. The problem of poverty can not be solved separately from the problems of unemployment, education, health and other social issues that explicitly closely related to the poverty. This study examines the influence of education and unemployment on poverty in East Nusa Tenggara. The purpose of this study is expected to analyze how and how deeply the influence of the variables of education and unemployment on poverty in East Nusa Tenggara and thus expected to be used as instrument in determining policy in addressing the problem of poverty in East Nusa Tenggara. The data used in this research is secondary data obtained from the Central Statistics Agency (BPS). While the methods of analysis used in this study is the method of linear regression analysis of data panel with REM method by the help of software Eviews 6. The results of this study indicate that the educational variables that to measure the person’s ability to read and write has a significant negative effect on the level of poverty, while unemployment has variable positive and significant impact on poverty levels in East Nusa Tenggara.